ANALISIS SEMIOTIK RIFATERRE DALAM SERPIHAN SAJAK HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Rinda Eka Nur Cahyanti; Syamsun Syamsun; Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This research is about Semiotik Riffaterre analysis which is contained in the rhyme of Sapardi Djoko Damono (SJHBJ) Sapardi rainy month of June. Problems analyzed in this research are poetry structure, matrix, model, variant, hipogram, relevance and character education value contained in (SJHBJ). Based on the problem, this study aims to describe the physical structure of diction and inner tones, heuristic readings, hermeneutic readings, matrices, models, variants, hypogram, relevance and value of character education in (SJHBJ) by Sapardi Djoko DamonoThis research use desciptive qualitative approach. The source of this research data is the rhyme fragments of the June Rain by Sapardi Djoko Damono from 102 poems there are 15 poems with religious social themes that are analyzed the December rhymes, Voice, About a Dead Grave Guard, In Sick, Pilgrimage, I See the Dark Side to Side We, the Doctrine of Life, at the Cemetery, Walking Behind the Bodies, After Delivering The Bodies, The Flowers On The Page, Rhyme 2, At The Zoo, In My Doer, Death. Researchers use documentation techniques to obtain data. Then the data obtained is analyzed based on structural elements of poetry, After analyzed using semiotik Riffaterre, poetry also sought the relevance and value of character education based on religious social.After analyzing structural poetry, the result of physical structure of poetry is diction. This Diction includes the diction of Rain, Flower, Life, Lowering Head, Shoes, Whispering, Words and Prayer. In addition there is a physical structure there is also the inner structure, namely tone, this tone includes straightforward, patronizing, satirical, dictate and cynical. Riffaterre semiotics analysis obtained heuristic, hermeneutic, matrix, model, variant and hipogram readings, then renewed and sought the value of character education. Keywords: Poetry, Religious Social, Semiotic Riffaterre